Numerical Analysis of Flow Through Venturimeter with Variation of Neck Size to Determine Velocity Coefficient and Pressure Drop - Beshay, Zakaria Gaber Hanawy; Sin, Sokunthea; Raja, Waleed A. (jurnal matematika, 2025)
Purpose of the study: This study aims to analyze the effect of variations in the size of the venturimeter neck on the velocity coefficient and pressure drop using a numerical simulation method. Methodology: The method used in this study is numerical simulation using SolidWorks 2014 software. The simulated venturimeter model has a neck length variation of 20 mm and 30 mm, with a throat diameter of 10 mm. The fluid used is water with a temperature of 25°C, and the simulation is carried out in the Reynolds number (Re) range of 1000 to 5000. Main Findings: The results of the study showed that the greater the velocity of the incoming fluid, the Reynolds number, flow rate, and pressure drop also increased. In addition, the difference in the length of the venturimeter neck affects the pressure drop, where the venturimeter with a longer neck experiences a greater pressure drop due to the longer duration of the fluid flow. The resulting velocity coefficient is also influenced by the velocity of the incoming fluid, where the higher the velocity, the greater the flow rate value. Novelty/Originality of this study: The novelty in this research lies in the numerical approach in analyzing the relationship between the venturimeter neck size and the velocity coefficient and pressure drop. This approach allows faster and more efficient calculations compared to conventional experimental methods, thus contributing to the development of more accurate and applicable fluid flow measurement techniques.